2010
DOI: 10.1136/ard.2010.129577m
|View full text |Cite
|
Sign up to set email alerts
|

The extent of the anti-citrullinated protein antibody repertoire is associated with arthritis development in seropositive arthralgia patients

Abstract: Purpose Anti-citrullinated protein antibodies (ACPA) are probably involved in the pathogenesis of rheumatoid arthritis. During the course of disease epitope spreading might occur. In this study, the ACPA repertoire of arthralgia patients and the association with arthritis development were studied. Methods 244 arthralgia patients positive for anti-cyclic citrullinated peptide antibodies (aCCP) and/or IgM rheumatoid factor, without clinical symptoms of arthritis were included. Arthritis was defi ned as the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 0 publications
5
50
0
Order By: Relevance
“…Antibodies to immunodominant peptides from established RA autoantigens were also measured, including citrullinated α-enolase (amino acids 4–21: KIHA-Cit-EIFDS-Cit-GNPTVE) (CEP-1),26–30 citrullinated vimentin (amino acids 60–75: VYAT-Cit-SSAV-Cit-L-Cit-SSVP)21 27 31–34 and citrullinated fibrinogen β chain (amino acids 36–52: NEEGFFSA-Cit-GHRPLDKK) 21 27 31 33. Serum samples from patients and controls were analysed for antibodies to these peptides by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies to immunodominant peptides from established RA autoantigens were also measured, including citrullinated α-enolase (amino acids 4–21: KIHA-Cit-EIFDS-Cit-GNPTVE) (CEP-1),26–30 citrullinated vimentin (amino acids 60–75: VYAT-Cit-SSAV-Cit-L-Cit-SSVP)21 27 31–34 and citrullinated fibrinogen β chain (amino acids 36–52: NEEGFFSA-Cit-GHRPLDKK) 21 27 31 33. Serum samples from patients and controls were analysed for antibodies to these peptides by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Although ACPA can be detected many years before the onset of symptoms of RA,21 22 emerging data indicate that it is unlikely that predictive algorithms on the basis of the recognition of specific citrullinated epitopes will be helpful, as studies performed in different populations revealed that parallel to a rise in the ACPA titre no specific reactivity could be identified that associated with the precipitation of disease 23–25. Likewise, clustering of these reactivities does not seem to provide additional information regarding the clinical phenotype of RA, for example, with respect to the disease activity score, swollen or tender joint counts26 27 or regarding the prediction of disease evolution in the pre-RA stage such as is present in patients with ACPA-positive arthralgia 24. Also, current data do not indicate added value of ACPA fine specificity testing in the prediction of radiological progression in the RA population.…”
Section: Maturation Of the Acpa Responsementioning
confidence: 70%
“…Indeed, there is also evidence for the presence of some of these particular epitopes, e.g., fibrinogen [43], vimentin [44], and alpha-enolase [45], in synovial tissue, which is the target organ in RA. Interestingly, the sera from patients with higher levels of ACPA can recognize more citrullinated epitopes [46], while ACPA levels also increase toward the disease onset [38]. Recently, van der Woude et al showed that ACPA in RA patients recognized more citrullinated epitopes than ACPA in UA patients [47].…”
Section: Acpa Isotypesmentioning
confidence: 98%
“…Furthermore, the ACPA repertoire in some patients with arthralgia is expanded. However, patients with an extended ACPA repertoire in the context of higher anti-CCP levels, but not specific citrulline peptide recognition, have a higher risk of developing arthritis [46]. From these data, we can conclude that epitope spreading is an ACPA characteristic which occurs in disease evolution.…”
Section: Acpa Isotypesmentioning
confidence: 98%